The first record of the wolf spider subfamily Zoicinae from China (Araneae: Lycosidae), with the description of two new species - Li, Zongxu; Wang, Lu-Yu; Zhang, Zhi-Sheng (Zootaxa, 2013)
The subfamily Zoicinae Lehtinen & Hippa, 1979 is here first recorded from China with the description of a new species in the genus Zoica Simon, 1898, Z. unciformis sp. nov. from Wild Elephant Valley (Yunnan) and a new species in the genus Lysania Thorell, 1890, L. deangia sp. nov., from a rubber plantation in Nangsang Village (Yunnan). Lysania pygmaea Thorell, 1890 is recorded for the first time in China, from three localities in Yunnan and Guangxi and is redescribed here.